Origin and originality of John Calvin's 'Harmony of the Law', the expository project on Exodus-Deuteronomy (1559-1563) - E. A. de Boer (Acta Theologica)
John Calvin’s plan to study Exodus, Leviticus, Numbers, and Deuteronomy in the form of a Harmony on the Last Four Books of Moses was conceived in the weekly Bible studies of the joint ministers of Geneva. A surviving manuscript of Calvin’s introductory exposition to the series, studied here for the first time since the 16th century, reveals intriguing details on the conception and execution of this plan. It also sheds light on the history of the congrégations, this fascinating example of concentration on the Bible in Geneva, on the co-operation of the ministers, and on Calvin’s role as the moderator of the Company of Pastors. The origin of the Harmony idea is an adaptation of the Gospel Harmonies. Calvin’s approach is highly original in the history of exegesis. The text of the congrégation points to Calvin’s reading of the commentary of the Lutheran Martin Borrhaus and, possibly, of Johannes Brenz’ commentary on Exodus.